A heap of killing [large type] - Vaughan, Robert, 1937-2024 (Vaughan, Robert, 1937-2024. Lucas Cain book, 2024)
"First introduced in Vaughan's A Rambling Man, Lucas Cain is back in the saddle, searching for some peace of mind and some solace after the loss of his wife and newborn child. He has continued his traveling from town to town, an itinerant lawman focused on capturing the bad guys for whatever amount is on the wanted papers for them. Local sheriffs and marshals, though initially wary of him, come to love him because he does what he does without pay -- other than the reward money. Cain finds himself in some tough spots, but always manages to stay one step -- and one fast bullet -- ahead of the outlaws he seeks. Dudley Stewart and his gang just might be the ones to stop that, though . . . On a lazy crime spree throughout the southwest, Stewart and his renegades have, up to now, been cutting a path of death, destruction, and loss through many a town . . . until Lucas Cain gets wind of their actions and gets it into his head to end the reign of terror with a hail of bullets . . ."--